Where do we stand now? mouse early embryo patterning meeting in Freiburg, Germany (2005) - Hiiragi, Takashi; Alarcon, Vernadeth B.; Fujimori, Toshihiko; Louvet-Vallee, Sophie; Maleszewski, Marek; Marikawa, Yusuke; Maro, Bernard; Solter, Davor (The International journal of developmental biology, 2006)
Mechanism underlying mammalian preimplantation development has long been a subject of controversy and the central question has been if any "determinants" play a key role in a manner comparable to the non-mammalian "model" system. During the last decade, this issue has been revived (Pearson, 2002; Rossant and Tam, 2004) by claims that the axes of the mouse blastocyst are anticipated at the egg ("prepatterning model"; Gardner, 1997; Gardner, 2001; Piotrowska et al., 2001; Piotrowska and Zernicka-Goetz, 2001; Zernicka-Goetz, 2005), suggesting that a mechanism comparable to that operating in non-mammals may be at work. However, recent studies by other laboratories do not support these claims ("regulative model"; Alarcon and Marikawa, 2003; Chroscicka et al., 2004; Hiiragi and Solter, 2004; Alarcon and Marikawa, 2005; Louvet-Vallee et al., 2005; Motosugi et al., 2005) and the issue is currently under hot debate (Vogel, 2005). Deepening our knowledge of this issue will not only provide an essential basis for understanding mammalian development, but also directly apply to ongoing clinical practices such as intracytoplasmic sperm injection (ICSI) and preimplantation genetic diagnosis (PGD). These practices were originally supported by a classical premise that mammalian preimplantation embryos are highly regulative (Tarkowski, 1959; Tarkowski, 1961; Tarkowski and Wroblewska, 1967; Rossant, 1976), in keeping with the "regulative model". However, if the "prepatterning model" is correct, the latter will require critical reassessment.